2015
DOI: 10.1002/chem.201405998
|View full text |Cite
|
Sign up to set email alerts
|

Unusually Short Chalcogen Bonds Involving Organoselenium: Insights into the Se–N Bond Cleavage Mechanism of the Antioxidant Ebselen and Analogues

Abstract: Structural studies on the polymorphs of the organoselenium antioxidant ebselen and its derivative show the potential of organic selenium to form unusually short Se⋅⋅⋅O chalcogen bonds that lead to conserved supramolecular recognition units. Se⋅⋅⋅O interactions observed in these polymorphs are the shortest such chalcogen bonds known for organoselenium compounds. The FTIR spectral evolution characteristics of this interaction from solution state to solid crystalline state further validates the robustness of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
105
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(117 citation statements)
references
References 64 publications
10
105
0
2
Order By: Relevance
“…has become a prominent topic in structural chemistry, and it has been recognized that ChB exhibits distinct directionality features compared with halogen bonds . Our recent study on the unusually short Se⋅⋅⋅O chalcogen bonds in the organoselenium antioxidant ebselen and its polymorphs by using X‐ray charge density analysis and FTIR spectral evolution (upon the formation of ChB during crystal nucleation) revealed the potential role of Se⋅⋅⋅O chalcogen bonding in the Se−N bond cleavage mechanism during the drug action of ebselen . Our results also established the occurrence of a robust and directional supramolecular synthon formed by a Se⋅⋅⋅O chalcogen bonded ring motif (analogous to the one in Figure ).…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…has become a prominent topic in structural chemistry, and it has been recognized that ChB exhibits distinct directionality features compared with halogen bonds . Our recent study on the unusually short Se⋅⋅⋅O chalcogen bonds in the organoselenium antioxidant ebselen and its polymorphs by using X‐ray charge density analysis and FTIR spectral evolution (upon the formation of ChB during crystal nucleation) revealed the potential role of Se⋅⋅⋅O chalcogen bonding in the Se−N bond cleavage mechanism during the drug action of ebselen . Our results also established the occurrence of a robust and directional supramolecular synthon formed by a Se⋅⋅⋅O chalcogen bonded ring motif (analogous to the one in Figure ).…”
Section: Introductionsupporting
confidence: 58%
“…Whereas, in this report, we examine the molecular complexes of riluzole as a rare series of examples for MCCs that recurrently exhibit S⋅⋅⋅O chalcogen bonded supramolecular recognition units, with focus on their strength, nature, electronic origin, and potential implications in crystal engineering and supramolecular chemistry. Although this study is a thematic continuation of our recent work on Se⋅⋅⋅O chalcogen bonded R(5) ring motifs in organoselenium antioxidants, to our knowledge, this is the first experimental report that shows analogous sulfur chalcogen bonding forming a robust and directional intermolecular interaction motif (supramolecular synthon). As the sulfur ChBs are clearly secondary interactions compared with the strong classical HBs present in this series of crystal structures, we have also analyzed the role of S⋅⋅⋅O ChBs in the packing of crystal structures which are devoid of such HBs.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…[8] This is shown in the structure of 4 in Scheme 2w ith average Se···O distances of 2.5 a nd CÀH···O distances of 2.35 . In GPx, nitrogen moieties of at ryptophane (Trp158) and of ag lutamine (Gln80) residue stabilize the selenium atom during the redox process.R ecent investigations on the mechanism of action of ebselen and related compounds revealed that the initial reaction of ebselen with thiols,such as GSH, leads to the formation of selenenyl sulfides,w hich are further stabilized by non-covalent selenium-oxygen interactions as shown in compound 7 in Scheme 2.…”
Section: Angewandte Highlightsmentioning
confidence: 99%
“…9,10,11,12,13,14 Over the past few years other non-conventional noncovalent interactions have gained attention, such as tetrel bonding, 15,16,17,18,19 pnictogen bonding, 20,21,22,23,24,25,26,27,28,29,30,31 chalcogenide bonding, 32,33,34,35,36,37,38,39,40,41,42,43,44 and even aerogen bonding. 45 All follow the same bonding scheme, namely a -hole, 46 which can be viewed comparably to hydrogen bonding: X-D … A, where X is any atom, D is the donor atom and A is the acceptor atom.…”
Section: Introductionmentioning
confidence: 99%